Community Structure of Seagrass in Coastal Waters of Bahoi Village, West Likupang Sub-district, North Minahasa Regency, North Sulawesi Province - Tolule, Kurnia; Kambey, Alex D.; Rondonuwu, Ari B. (Jurnal Ilmiah PLATAX, 2015)
This study was aimed at revealing the structure of seagrass community in the coastal waters of Bahoi Village, West Likupang Sub-district, District of North Minahasa, North Sulawesi Province. Samples collection was conducted during the lowest tide period by deploying line transect and quadrate. Eight species of seagrasses were identified on this study, including species as follow: Enhalus acoroides, Thalassia hempricihii, Cymodocea rotundata, C. serrulata, Syringodium isoetifolium, Hlodule pinifolia, H. uninervis and Halophila ovalis. The highest density value ( 112.16 individual/m2) was calculated from transect III data on S. isoetifolium species. In term of relative density value, S. isoetifolium also has the highest value (35.176 %). Index dominance (C) was calculated as well from transect III data (0.477) while the highest diversity index  (H’) was calculated from transect I data (1.724). Keyword : structure, Analysis, seagrass ABSTRAK Penelitian ini bertujuan mengkaji struktur komunitas lamun di perairan pantai Desa Bahoi Kecamatan Likupang Barat Sulawesi Utara.Pengambilan sampel  dilaksanakan sekali pada saat surut terendah, data dikumpulkan berdasarkan garis transek dan kuadrat. Jenis lamun yang ditemukan dalam keseluruhan kuadrat di lokasi penelitian berjumlah 8 spesies yaitu : Enhalus acoroides, Thalassia hemprichii, Cymodocea rotundata, Cymodocea serrulata, Syringodium isoetifolium, Halodule pinifolia, Halodule uninervis, dan Halophila ovalis. Kepadatan individu tertinggi terdapat pada transek III yaitu spesies Syringodium isoetifolium 112,16 ind/m2. Kepadatan relatif tertinggi terdapat pada spesies Syringodium isoetifolium (35,176 %). Indeks dominasi (C) yang tertinggi terdapat pada transek III 0.477 indeks keanekaragaman spesies (H’) yang tertinggi pada transek I 1.724. Keyword : structure, Analysis, seagrass 1Mahasiswa Program Studi MSP FPIK-UNSRAT 2Staf pengajar Fakultas Perikanan dan Ilmu Kelautan Universitas Sam Ratulangi